Metode Geographically Weighted Panel Regression (GWPR) untuk Memodelkan Jumlah Penduduk Miskin di Provinsi Jawa Timur pada Tahun 2019 – 2022 - 10060118019, Santi Novi Ramadhanty (Bandung Conference Series: Statistics, 2025)
Abstract. Panel data is a combination of time series data and cross-sectional data. The purpose of panel data regression methods is to construct a regression model that can explain the influence of independent variables on the dependent variable across several sectors observed over a specific period in a study. In estimating the model, panel data regression methods use three types of estimators: the Common Effect Model, Fixed Effect Model, and Random Effect Model, from which the best model will later be selected. If, in the analysis, spatial data or observation locations are involved and this method is still used without adjustments, it may lead to a violation of assumptions, particularly spatial heterogeneity. Therefore, an approach to address spatial data issues is by using Geographically Weighted Regression (GWR). A method called Geographically Weighted Panel Regression (GWPR) needs to be developed, which aims to comprehensively integrate location (cross-sectional data) and observations over time. The GWPR analysis in this study uses an adaptive kernel because this type of kernel provides a different bandwidth for each observation point. This is due to its functional ability to adapt to the specific conditions of each observation point. By selecting the model based on the lowest AIC, highest R², and lowest Cross Validation (CV) values, the optimal bandwidth is incorporated into the model, resulting in a weighted or calibrated model. Abstrak. Data Panel merupakan data gabungan antara data time series dan data cross-section. Metode regresi data panel bertujuan untuk membentuk suatu model regresi yang dapat memodelkan pengaruh bebas terhadap variabel terikat dalam beberapa sektor yang diamati selama periode waktu tertentu dari suatu penelitian. Dalam mengestimasi model metode regresi data panel memiliki 3 estimasi yaitu : Common Effect Model, Fixed Effect Model dan Random Effect Model yang nantinya akan dipilih model mana yang terbaik. Jika dalam analisis ini terdapat lokasi pengamatan atau data spasial dan dipaksakan untuk menggunakan metode ini, maka akan terjadi pelanggaran asumsi yaitu heterogenitas spasial, oleh karena itu ada pendeketan untuk mengatasi adanya data spasial dengan menggunakan Geographycally Weighted Regression (GWR). Perlu dikembangkannya suatu metode yang disebut Geographycally Weighted Panel Regression (GWPR) yang bertujuan untuk menggabungkan secara keseluruhan lokasi (cross sectional) dan observasi. Analisis GWPR dalam penelitian ini menggunakan adaptive kernel dikarenakan kernel ini memiliki bandwidth yang berbeda untuk setiap titik lokasi pengamatan, hal ini disebabkan kemampuan fungsinya yang dapat disesuaikan dengan kondisi titik – titik pengamatan. Dengan pemilihan model dengan melihat nilai AIC paling rendah, nilai R2 paling tinggi dan nilai Cross Validation (CV) paling minimum, nilai bandwidth optimum ini dimasukan kedalam model, sehingga model yang dihasilkan sudah terboboti.